Quantitative assessment of changes in diffusion tensor imaging (DTI) metrics along the courses of the cortico‐ponto‐cerebellar tracts secondary to supratentorial human brain glial tumors - Mirbagheri, Saeedeh (Cancer Rep (Hoboken), 2018)
BACKGROUND: The cortico‐ponto‐cerebellar tract (CPCT) is the largest projection pathway, which synapses at the pons. Remote effects of supratentorial brain tumors have not been evaluated along the infratentorial course of the CPCT. AIM: The purpose of this study is to evaluate the possible lateralization of the diffusion tensor metrics of the affected CPCT in patients with supratentorial brain tumor. METHODS AND RESULTS: We included 39 patients with 29 left‐sided tumors (LST) and 10 right‐sided tumors, retrospectively. We measured the magnitude of changes of the fractional anisotropy (FA) and apparent diffusion coefficient (ADC) values of the CPCT prior to the brain surgery at the level of crus cerebri and middle cerebellar peduncle. Regions of interest (ROIs) were placed on the lateral side of crus cerebri, and ROI‐1 (anterior 1/3), ROI‐2 (middle 1/3), ROI‐3 (posterior 1/3), and ROI‐4 were placed at the level of middle cerebellar peduncle. We hypothesized that there would be decreased FA and increased ADC values of the ipsilesional CPCT compared with contralesional CPCT. Ipsilesional FA values were decreased with simultaneous increased ADC value along the CPCT compared with contralesional CPCT in following ROIs, ROI‐1 (LST FA: P = .005, ADC: P = .037) and ROI‐3 (LST FA: P = .049, ADC: P = .049), respectively. Affected ROI‐4 in LST cases also showed lower FA values, although not statistically significant. CONCLUSION: We observed a statistically significant FA value decrease and ADC increase along the left ROI‐1 and ROI‐3 as well as the nonstatistically significant FA decrease of the left ROI‐4 at the second neuron level when there was a related supratentorial tumor. These findings are suggestive of presynaptic and postsynaptic microstructural changes of these tracts following the presynaptic involvement by a primary supratentorial brain tumor.